Oxidative stress and genotoxicity in 1,4-dioxane liver toxicity as evidenced in a mouse model of glutathione deficiency - Chen, Ying; Wang, Yewei; Charkoftaki, Georgia; Orlicky, David J.; Davidson, Emily; Wan, Fengjie; Ginsberg, Gary; Thompson, David C.; Vasiliou, Vasilis (The Science of the total environment, 2022)
1,4-Dioxane (DX) is a synthetic chemical used as a stabilizer for industrial solvents. Recent occurrence data show widespread and significant contamination of drinking water with DX in the US. DX is classified by the International Agency for Research on Cancer as a group 2B carcinogen with the primary target organ being the liver in animal studies. Despite the exposure and cancer risk, US EPA has not established a drinking water Maximum Contaminant Level (MCL) for DX and a wide range of drinking water targets have been established across the US and by Health Canada. The DX carcinogenic mechanism remains unknown; this information gap contributes to the varied approaches to its regulation. Our recent mice study indicated alterations in oxidative stress response accompanying DNA damage as an early change by high dose DX (5000 ppm) in drinking water. Herein, we report a follow-up study, in which we used glutathione (GSH)-deficient glutamate-cysteine ligase modifier subunit (Gclm)-null mice to investigate the role of redox homeostasis in DX-induced liver cytotoxicity and genotoxicity. Gclm-null and wild-type mice were exposed to DX for one week (1000 mg/kg/day by oral gavage) or three months (5000 ppm in drinking water). Subchronic exposure of high dose DX caused mild liver cytotoxicity. DX induced assorted molecular changes in the liver including: (i) a compensatory nuclear factor erythroid 2-related factor 2 (NRF2) anti-oxidative response at the early stage (one week), (ii) progressive CYP2E1 induction, (iii) development of oxidative stress, as evidenced by persistent NRF2 induction, oxidation of GSH pool, and accumulation of the lipid peroxidation by-product 4-hydroxynonenal, and (iv) elevations in oxidative DNA damage and DNA repair response. These DX-elicited changes were exaggerated in GSH-deficient mice. Collectively, the current study provides additional evidence linking redox dysregulation to DX liver genotoxicity, implying oxidative stress as a candidate mechanism of DX liver carcinogenicity. [Display omitted] •1,4-Dioxane evoked transient compensatory NRF2 antioxidant response in mouse livers.•CYP2E1 was induced by 1,4-dioxane, accompanied by oxidative stress in mouse livers.•GSH deficiency escalated 1,4-dioxane-induced oxidative DNA damage in mouse livers.•Redox dysregulation may play a causal role in 1,4-dioxane liver genotoxicity.